Investigations of skeletal anomalies in triploid Atlantic salmon (Salmo salar L. 1758) in freshwater : with particular focus on lower jaw deformity (LJD) - Amoroso, G (2016)
Triploid Atlantic salmon are a valuable part of production in Tasmania. In fact, not undergoing sexual maturation, triploids are used to ensure appropriately sized harvest fish all year round. Nevertheless, triploids tend to develop a higher prevalence of skeletal anomalies than diploids affecting mainly the lower jaw and the vertebral column and impacting fish performance, welfare and value deleteriously. The general intent of this PhD research project was to make a useful contribution to Atlantic salmon industry in order to understand and find a possible solution or mitigate the problem of skeletal anomalies of obvious relevance to economic efficiency as well as animal welfare in Tasmania and worldwide. This research explored the occurrence of several skeletal anomalies in farmed diploid and triploid Atlantic salmon in freshwater that represent a critical phase in development. The aims were to improve our knowledge on occurrence and causative factors of skeletal anomalies in triploids (and diploids) and in particular of lower jaw deformity (LJD), a skeletal anomaly mainly affecting triploid Atlantic salmon, and to understand the molecular mechanisms underlying it. Two experiments (the first containing two sub-experiments) and an extensive molecular investigation have been undertaken during this PhD research project in order to produce valuable information and fulfil the predetermined aims. In the first experiment, diploids and triploids were maintained in controlled conditions for nine months (from incubation to 60 g) and repeatedly screened (visually and by x-ray) for the occurrence of several categories of skeletal anomalies (i.e. lower jaw anomalies, opercular shortening, spinal anomalies) and the effect of standard and elevated temperature regimes (14 and 18 ¬¨‚àûC) on prevalence of skeletal anomalies was tested in the pre-smolt stage (8-60 g). This experiment showed that LJD started to be displayed at 8-10 g and the prevalence increased only in triploids up to 11% at 60 g implying that occurrence can be ...